Comparative Study of The Influence of Disaster Knowledge on Preparedness Attitudes in Dealing with Disasters in Geography and Public Health Education Students - Utomo, David Hario; Rahman, MS Khabibur; Kurniaaji, Bayu; Rohsulina, Pranichayudha (International Journal for Disaster and Development Interface, 2024)
Knowledge is the key factor and key to preparedness. Preparedness is one part of the disaster management process and in the concept of disaster that is developing today. The objectives of this study include: 1) To determine the level of disaster knowledge in Geography and Public Health Education students.2) To find out the comparison of preparedness attitudes in dealing with disasters between Geography Education and Public Health students.3) To know the difference in the influence of disaster knowledge on preparedness attitudes in dealing with disasters. The method used in this study is a quantitative method. The sampling technique used is the saturated sampling technique or total sampling. The data collection techniques in this study are through observation, questionnaires, interviews, and documentation. The data analysis technique uses percentage descriptive analysis, simple linear regression analysis to determine the influence of variable (X) on variable (Y) using the t and R2 test hypothesis test. The results of this study are: 1) The level of disaster knowledge of geography education and public health students is both in the high category, 2) The level of preparedness attitudes of geography and public health education students is both in the high category, 3) The results of hypothesis testing with the t-test and the determination coefficient test, there is a positive influence of disaster knowledge on the attitude of preparedness in dealing with disasters in geography education students and Public Health. This means that the higher the knowledge of disasters, the higher the preparedness attitude of residents in dealing with landslide disasters.